2012
DOI: 10.5858/arpa.2011-0217-cp
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Diagnostic Correlation With Breast Imaging Findings: A College of American Pathologists Q-Probes Study of 48 Institutions

Abstract: Context.—Correlation of radiologic and pathologic findings is important for optimal management of patients with image-guided breast biopsies. Objectives.—To (1) evaluate the rates of radiologic and pathologic correlation in breast needle core biopsies, (2) evaluate laboratory and radiology practices associated with greater correlation rates, and (3) determine the rates at which the lack of radiologic-pathologic correlation is documented in pathology reports. Design.—The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Michael et al and O Idowu et al in their study found the rate of radiologic‐pathologic concordance was as high as 94.5% …”
Section: Results Of Concordance Between Birads and Pathological Findingssupporting
confidence: 90%
“…Michael et al and O Idowu et al in their study found the rate of radiologic‐pathologic concordance was as high as 94.5% …”
Section: Results Of Concordance Between Birads and Pathological Findingssupporting
confidence: 90%
“…The College of American Pathologists, as part of its voluntary Q-Probes quality assessment program, recently reported a retrospective pathology-imaging correlation study from 48 institutions [58]. This study is an important step in the right direction but was restricted to self-reported pathology departmental processes from core needle biopsies and did not purport to evaluate routines involving surgical excision specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Third, an interdisciplinary conference provides a forum for multiple radiologists and pathologists to review the same findings and come to a consensus opinion [20]. Often, the pathologists can provide critical quantitative and qualitative information regarding the biopsy, which is essential to determining concordance, but may not be communicated in the report.…”
Section: Discussionmentioning
confidence: 99%